TOKOH DAN PENOKOHAN DALAM TEKS CERPEN KARYA SISWA KELAS IX SMP NEGERI 21 PADANG - Aisyah, Indri; Abdurrahman, Abdurrahman (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT This research was conducted to describe the types of figures and techniques for the presentation of the characters used in the short text of grade IX SMP Negeri 21 Padang. This type of research is qualitative with descriptive method. The data of this study are qualitative data in the form of the use of types of figures and techniques for the presentation of the character's character in the students' short stories. The data were analyzed by steps, namely (1) the researcher identified a general description of the data analyzed as well as coding the text, (2) inventorying the research data coding, (3) analyzing the characters and characterizing short story texts by students, (4) interpreting data based on theory and conclude the findings then write the report. Based on the results of the study, the results of the research there were two. First, the types of figures that tend to be used by grade IX SMP Negeri 21 Padang in the short story texts written are additional figures, protagonists, simple characters, static figures and neutral figures. Second, the technique of presenting figures that tends to be used by IX grade students at SMP Negeri 21 Padang in writing short stories is analytical techniques, action techniques, and word techniques.                Kata Kunci: Tokoh, Penokohan, Teks Cerpen